THE PSYCHOLOGICAL INFLUENCE OF THE SOCIAL ENVIRONMENT ON THE CHOICE OF CLOTHING DEPENDING ON PROFESSIONAL ACTIVITY (Psychology Travelogs, 2024)
The article examines the influence of the social environment on the choice of clothing and its psychological consequences. It has been determined that cultural norms and the professional sphere affect a person's mental state and their choice of clothing, causing stress, anxiety and insecurity. The importance of understanding this influence for increasing self-awareness and adaptability in the workplace is highlighted. The need to develop strategies to support the psychological comfort of employees, which will reduce the level of stress and increase self-esteem, is noted.The importance of further research taking into account individual needs is emphasized. Specifying these aspects in recommendations to support the psychological comfort of employees will contribute to the improvement of the general emotional state. The relevance of the conducted detailed study and analysis of factors affecting the individual selection of clothing in a professional environment has become useful for developing more effective personnel management strategies and improving labor productivity. The study and analysis of the psychological influence of the social environment, cultural norms and professional standards on the choice of clothing is a key aspect in the formation of a person's style and well-being. The discrepancy between personal style and the demands of the social environment generates a number of negative psychological consequences, such as stress, anxiety and self-doubt, which can become an obstacle to effective work and enjoyment of it.In particular, it is important to focus further research on education and training on the development of psychological resilience and stress management, which will help employees better adapt to the demands of the professional environment and maintain emotional balance.
Keywords: psychological influence; social environment; choice of clothing; cultural norms; professional activity; psychological comfort; self-esteem